Fitokimia, Flavonoid, dan Aktivitas Antioksidan Jamur Sawit (Volvariella sp) - Dzul Fadly; Rosa Dhayan; Brigita Ratna Harsanti; Dea Malyana Putri; Nur Endah Saputri (Sarana Ilmu Indonesia (salnesia), 2021)
Palm mushroom (Volvariella sp) is an edible mushroom that grows on the empty palm oil bunches, where this waste is very abundant along with the increasing production of CPO (Crude Palm Oil) of the palm oil industry. This study aimed to determine phytochemicals, flavonoids, also their antioxidant activity. The investigation was conducted on aqueous water extract and ethanolic extract of palm mushrooms. It was revealed that palm mushrooms positively contained secondary metabolites, including flavonoids, tannins, saponins, and phenols. The ethanolic extract confirmed the highest total flavonoid content of 25,9 mg QE/g dw with an IC50 value of 19,14 ppm, then declared a powerful antioxidant among aqueous extract and BHT. It confirmed that this food could be an alternative as an antioxidant source.